A translation table for patient-centered comparative effectiveness research: guidance to improve the value of research for clinical and health policy decision-making. (May 2012) - Tunis, Sean R; Messner, Donna A; Mohr, Penny; Gliklich, Richard E; Dubois, Robert W
This article provides background and context for a series of papers stemming from a collaborative effort by Outcome Sciences, Inc., the National Pharmaceutical Council and the Center for Medical Technology Policy to use a stakeholder-driven process to develop a decision tool to select appropriate methods for comparative effectiveness research. The perceived need and origins of the 'translation table' concept for method selection are described and the legislative history and role of the Patient-Centered Outcomes Research Institute are reviewed. The article concludes by stressing the significance of this effort for future health services and clinical research, and the importance of consulting end-users – patients, providers, payers and policy-makers – in the process of defining research questions and approaches to them.